Efisiensi Perkebunan Kelapa Sawit di Provinsi Aceh - Irfan Irfan; Ardian Ardian; Yuliana Yuliana; Isthafan Najmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Oil palm plantations are part of the leading commodities in Aceh province which have an important contribution in terms of supporting the economy and welfare of farmers. In the plantation sector it is very important to measure the level of technical efficiency to find out the optimal level of production from the production input factors used. This study aims to analyze the technical efficiency of oil palm farming in Aceh Province. The analytical method used is the frontier production function with the return to scale Variabe Approach. The results of the study show that overall for four consecutive years there are six districts in Aceh province that have technically efficient palm oil production (Pidie, Aceh Utara, Langsa, with a technical efficiency score of > 7. The average level of technical efficiency for farmers is 0. 8795, the lowest tennis efficiency level is 0.7569 and the highest technical efficiency level is 0.9471